Barriers to expansion of cancer research: Data collection challenges at a single-institution in Rwanda. (March 2016) - Silverstein, Allison; Mugenzi, Pacifique; Lule, Joseph; Costas-Chavarri, Ainhoa
Highlights: We describe challenges in data collection at a single-institution in Rwanda. Difficulties in data collection compromise data quality and results. EMRs can improve standardized documentation in low resource settings. Need for improved data management at institutional level prior to national scale-up. Abstract: Introduction: While cancer is a leading cause of morbidity and mortality globally with an increasing burden on low- and middle-income countries (LMICs), these countries lack the appropriate funding and resources to care for cancer patients and conduct relevant research. The purpose of this study is to describe the challenges faced by a Rwandan research team looking to describe gastric cancer, the third most common cancer in terms of incidence and mortality in LMICs. We aim to use these lessons to not only highlight the need for growth in data management but also to provide suggestions on ways to achieve such improvement. Methods: A retrospective review at a single institution in Rwanda. Patient information was found and collected from eight different hospital sources for all patients diagnosed with gastric cancer or presenting with symptoms suggestive of possible gastric cancer etiology since October 2012. Results: The team identified 125 patients who were separated into 27 unique groups based on the sources in which they were found. The greatest number of sources in which any patient was found was five ( n = 1). 76.0% of patients were located in the EMR ( n = 95). Discussion: Challenges to obtain comprehensive patient information are prohibitive for the cancer research development needed in LMICs. In order to meet this need, documentation should be more standardized and reflect coordinated care. Through widespread implementation of institutional EMR systems, future scale up to national cancer registries that inform and reflect national cancer care plans is possible.